Combining various acupuncture therapies with multimodal analgesia to enhance postoperative pain management following total knee arthroplasty: a network meta-analysis of randomized controlled trials - Liu, Ningning; Liu, Gaihong; Chang, Xiaoli; Xu, Yingxue; Hou, Yi; Zhang, Dongbin; Wang, Lianzhu; Chen, Shaozong (Frontiers in Neurology, 2024)
Objective: This study aims to evaluate the efficacy and safety of various acupuncture treatments in conjunction with multimodal analgesia(MA) for managing postoperative pain and improving knee function in patients undergoing total knee arthroplasty (TKA), based on findings from clinical research indicating the potential benefits of acupuncture-related therapies in this context.Methods: We searched Web of Science, PubMed, SCI-hub, Embase, Cochrane Library, CBM, CNKI, Wanfang Data, and VIP to collect randomized controlled trials of acupuncture-related therapies for post-TKA pain. After independent screening and data extraction, the quality of the included literature was evaluated. The potential for bias in the studies incorporated in the analysis was assessed according to the guidelines outlined in the Cochrane Handbook 5.1. Network meta-analysis (NMA) was conducted using Revman 5.4 and Stata 16.0 software, with primary outcome measures including VAS, PPT, HSS and ROM. Furthermore, the interventions were ranked based on the SUCRA value.Results: We conducted an analysis of 41 qualifying studies encompassing 3003 patients, examining the efficacy of four acupuncture therapies (ACU, EA, TEAS, AAT) in conjunction with multimodal analgesia (MA) and MA alone.The VAS results showed no significant difference in efficacy among the five interventions for VAS-3 score. However, TEAS+MA (SMD:0.67;95%CI: 0.01,1.32) was more effective than MA alone for VAS-7 score. There was no significant difference in PPT score among the three interventions. ACU+MA (SMD:6.45;95%CI:3.30,9.60), EA+MA (SMD:4.89; 95%CI:1.46,8.32), TEAS+MA (SMD:5.31;95%CI:0.85, 9.78) were found to be more effective than MA alone for HSS score.For ROM score, ACU+MA was more efficacious than EA+MA, TEAS+MA, AAT+MA, MA.Regarding the incidence of postoperative adverse reactions, nausea and vomiting were more prevalent after using only MA.Additionally, the incidence of postoperative dizziness and drowsiness following ACU+MA (OR=4.98;95%CI:1.01,24.42) was observed to be higher compared to that after AAT+MA intervention.Similarly,the occurrence of dizziness and drowsiness after MA was found to be significantly higher compared to the following interventions: TEAS+MA (OR=0.36; 95%CI: 0.18, 0.70), AAT+MA (OR=0.20;95%CI: 0.08, 0.50).The SUCRA ranking indicated that ACU+MA, EA+MA, TEAS+MA, and AAT+MA displayed superior SUCRA scores for each outcome index, respectively.Conclusion: For the clinical treatment of post-TKA pain, acupuncture-related therapies can be selected as a complementary and alternative therapy.